(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study briefly describes Marketing Management factors of social responsibility i.e. product, survival, price and profit which are involved in the marketing practices in Cachar district, among them 96 unit under the study. Marketing has an important role to play in the growth and development of underdeveloped economy. A rapid development of an underdeveloped country it is possible only through the modern techniques of marketing. Importance of marketing goes on increasing in these countries with every growth in industrialization and urbanization because marketing is a significant tool for producing the goods and services at large scale and for selling this production successfully in the market. Marketing is considered to be the most important activity of all the business activities. It has become a necessity for the successful operation of all other business sources. In recent years, the functions of marketing have undergone tremendous changes. It is being recognized as a profession based on a systematic part of knowledge. These changes have increased the liabilities of marketing in international markets. It exercises a definite and extensive influence on our economic and social life styles. As a socio-economic institution a market-oriented company has to perform all tasks involved in the development and delivery of goods and services from production to consumption. As a social institution, marketing is responsible to deliver a standard of living and maximise life quality. Now life quality means not only the quantity and quality of consumer goods and services but also enriched quality of the environment.